The Imprint of Vegetation on Desert Dune Dynamics. Issue 21 (13th November 2019) - Lee, Dylan B.; Ferdowsi, Behrooz; Jerolmack, Douglas J.
Abstract: Here we demonstrate the qualitative and quantitative influence that vegetation has on stabilizing desert dunes. We use topographic data to isolate translation and deformation of dune patterns, upwind of and across a sharp gradient of vegetation, at White Sands dune field, New Mexico. Barchanoid dunes are unstable due to an aerodynamic surface wave instability. The dynamics of vegetated parabolic dunes are different; deformation becomes localized, and random, once plant density reaches a critical value associated with the barchanoid‐parabolic transition. Plants stabilize dunes not only by slowing them down but also by shutting off the fundamental mechanism that generates new sand waves and destabilizes dunes. Increasing plant density downwind increases vegetation‐induced form drag and results in decreasing dune migration rate. We suggest that similar biological modulation of pattern‐forming instabilities may also occur in other landscapes. Key Points: We determine the styles and rates of pattern deformation of migrating desert dunes We show that plants disrupt an aerodynamic dune‐forming instability This is a rare, quantitative demonstration of vegetation modulating both rate and form of landscape evolution